Analisis Kadar Albumin dan Profil Protein Ikan Toman (Channa Micropeltes) dari Kalimantan Selatan - Nia Kusumadewi; Nafach Olya Warasky; M. Awaluddin Padjrin; Andika Andika (Journal of Pharmaceutical and Sciences, 2026)
Toman fish (Channa micropeltes) is a freshwater fish widely found in Kalimantan and known for its high nutritional value, particularly its albumin and omega-3 fatty acid content. However, studies regarding the metabolite profile and albumin levels of this species are still limited compared with other snakehead fish species. This study aimed to analyze the protein profile and determine the albumin levels of toman fish collected from three regions in South Kalimantan, namely Barito Kuala, Banjarmasin, and Banjarbaru. Albumin extraction was carried out using the Ultrasonic-Assisted Extraction (UAE) method. Qualitative characterization of protein functional groups was performed using ATR-FTIR spectroscopy in the range of 4000–400 cm⁻¹, while quantitative determination of albumin levels was conducted using UV–Vis spectrophotometry at a wavelength of 642 nm with bromocresol green (BCG) reagent. The results showed that the highest albumin level was obtained from Banjarmasin samples (0.560 ± 0.0343 %w/w), followed by Barito Kuala (0.542 ± 0.0416 %w/w), whereas the lowest level was observed in Banjarbaru samples (0.431 ± 0.0261 %w/w). ATR-FTIR analysis confirmed the presence of albumin in all samples through the identification of characteristic amide I (~1650 cm⁻¹) and amide II (~1550 cm⁻¹) absorption bands. Statistical analysis indicated that differences in albumin levels among sampling locations were not statistically significant (p > 0.05), although numerical variations were observed and may be associated with environmental and habitat conditions. Overall, the combination of UV–Vis spectrophotometry and ATR-FTIR proved effective for the characterization and determination of albumin in Channa micropeltes.